Flow boiling in horizontal annuli outside horizontal smooth, herringbone and three-dimensional enhanced tubes. (November 2019) - Sun, Zhi-chuan; Li, Wei; Ma, Xiang; Ayub, Zahid; He, Yan
Highlights: The use of enhanced annulus improves the boiling heat transfer coefficient. Better heat transfer performance was found at xout = 0.6 for annuli with an annular width of 6.35 mm. Heat transfer deterioration will worsen as the annular gap size decreases. Annulus-side evaporation exhibits the higher thermal efficiency in comparison to the tube-side case. Abstract: Heat transfer and pressure drop measurements of R410A saturated flow boiling in horizontal annuli were performed at a saturation temperature of 6 °C over the mass flux range of 8–107 kg/(m 2 s). The inner tubes with the same inside diameter of 12.70 mm contain a smooth tube, a herringbone micro-fin tube and a 1EHT tube (a dimpled tube enhanced by petal-shaped background patterns). In this study, the test section is a typical double-tube type heat exchanger and the emphasis is focused on the effects of mass flux, vapor quality, annular width and surface structures on the annulus-side heat transfer. Wilson plot method was adopted to ensure the correction factor of water-side coefficient of 1EHT tube. For flow boiling tests in annuli with an annular gap of 6.35 mm, both the evaporating coefficient and pressure drop increase as the mass velocity increases. Better thermal performance was seen at a outlet vapor quality of 0.6. In this case, the heat transfer rate ratio of enhanced annulus to smooth annulus is 1.7–2.5 for the herringbone micro-fin tube and 1.4–1.7 for the 1EHT tube, respectively. When the annular spacing decreases, heat transfer deterioration will worsen accompanied with a sudden drop in boiling heat-transfer coefficient. Besides, a comparison of flow boiling characteristics of annulus-side and tube-side heat transfer was made. The annulus-side heat transfer coefficient is much larger than that of tube-side case.